What is the concept of innovation for public school principals of Baku - Nadirzada, Narmin (Technium Social Sciences Journal, 2022)
Management is a form of social interaction that governs, influences, directs, and regulates cultural, social, and legal relationships among people in the interests of the state, society, and the group. The most important issue in the management of modern schools in the innovation environment is the transfer of the traditional school to the novel educational institution and to implement developmental strategies. The purpose of the paper is to analyze innovative approaches that principals use in public schools of Azerbaijan and to evaluate, describe and interpret the situation in its original environment. Analysis of the interviews with school principals revealed that technological development is the most effective factor that creates the need for innovation. School administrators mentioned different kinds of challenges in the process of innovation such as : teachers’ insufficiency, age group of staff, parent contingent of the school, lack of communication with staff, lack of teachers and equipment, , inadequate functioning of school-parent associations and school budgets. In this context, principal with the contribution of all stakeholders should be in line with the culture of their school and manage the innovation process in line with the vision of the future.